Insights into the influence of canine breed on proteomics of the spermatozoa and seminal plasma - Araujo, Michelle Silva [UNESP]; de Oliveira Henriques Paulo, Otávio Luís [UNESP]; Scott, Caroline [UNESP]; Paranzini, Cristiane Sella [UNESP]; Codognoto, Viviane Maria [UNESP]; de Paula Freitas Dell'Aqua, Camila [UNESP]; Papa, Frederico Ozanam [UNESP]; de Souza, Fabiana Ferreira [UNESP] (Elsevier, 2022)
This study aimed to characterize the proteome of spermatozoa and seminal plasma of 4 purebred dogs (Golden Retriever, Great Dane, Bernese Mountain Dog, and Maremmano-Abruzzese Sheepdog). The ejaculate of 13 dogs was collected, and sperm characteristics were subjectively evaluated. Seminal plasma and sperm cells were separated and prepared individually for mass spectrometry. Data were evaluated by univariate and multivariate statistical analysis. A total of 162 proteins were identified, 47 in spermatozoa, 109 in seminal plasma, and 6 in both samples. Serum albumin in spermatozoa and tubulin alpha-3E chain, acrosin binding protein, and tubulin alpha-3 chain in plasma seminal were statistically relevant. Serum albumin and acrosin binding protein improve the sperm capacitation, acrosome reaction, and seminal quality. The tubulin family proteins are related to structural cell organization and flagella movement, and their presence in seminal plasma may be related to sample handling. According to cluster formation, a high association was observed among Bernese Mountain Dog and Great Dane, Golden Retriever, and Maremmano-Abruzzese Sheepdog for sperm proteins. For seminal plasma proteins, Bernese Mountain Dog, Great Dane, and Maremmano-Abruzzese Sheepdog were related. Further studies on breed-specific proteins in the semen of purebred dogs need to be performed to clarify its fertility roles. Significance: For the first time spermatozoa proteins of dogs are described. The comparison of spermatozoa and seminal plasma proteins of four purebred dogs were performed. These results supporting that differences in semen protein profile of different canine breeds exist, which can improve the biotechnologies of reproduction in this species.
Keywords: Canine fertility; Mass spectrometry; Protein; Purebred dog; Semen